Numerical Simulation of Continuous Tilting Transition of Tiltrotor Aircraft - WU Weiwei; MA Cunwang; ZHANG Lian; SUN Kaijun (Hangkong gongcheng jinzhan, 2021)
The aerodynamic configuration of the tiltrotor aircraft is constantly changed during the tilting transition process, and the aerodynamic characteristics is of strongly nonlinear characteristics.Aiming at the complex states of continuous tilting transition for the tiltrotor aircraft, the grid system suitable for the simulation of the continuous tilting transition for the tiltrotor aircraft is established through the moving embedded grid and local coordinate system theory, and based on the RANS equation, a CFD method suitable for unsteady flow field analysis with strongly nonlinear aerodynamic characteristics is established.The method is used to simulate the aerodynamic characteristics of the continuous tilt transition for a certain type tiltrotor aircraft from helicopter mode to fixed wing mode.The results show that the aerodynamic characteristics of the rotors and the airframe have the same trend with the increase of the rotor tilt angle for different tilt transition time.As the rotor tilt angle increase, the lift coefficient of airframe is firstly increased and then decreased, and achieved the maximum value near 40°, which is increased by about 30%in comparison with the initial state and level flight.As the rotor tilt angle, with the increased of collective pitch angle and forward flight speed linearly, the rotor tension coefficient and its vertical component gradually are decreased gradually.With the linear increase of the rotor tilt angle and forward flight speed, the total lift of the tiltrotor aircraft can be kept near the target value by using a suitable nonlinear variation curve of the collective pitch angle.